Pengaruh Beban Pendingin Terhadap Temperatur Sistem Pendingin Siklus Kompresi Uap Dengan Penambahan Kondensor Dummy Tipe Multi Helical Coil Sebagai Water Heater - Sarwo Fikri; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Increasing the efficiency is one of methods to assist the Indonesian government’s planning in saving energy. One of them is to combine two functions from two different devices become a new device that have two functions. For instance, Split AC is used to cool the room. The adding of dummy condenser in Split AC is using heat exhaust at condenser that functioned as water heater. In this research, it is aimed to identify the effect of adding the dummy condenser toward cooler load. The method used in this research was design and experimental method. Based on the test, When cooler load was given to the room, the more the burden of cooling given, the higher refrigerant temperature to be thus heat water temperature was higher as well. During the operation 120 minutes, it obtained that heat water temperature was 84,110C and refrigerant temperature was 64,770C.Keywords : Dummy Condenser, Temperature, Cooler load and water valve faucet.